PERANAN NOTARIS SEBAGAI SAKSI (SYÂHID) TERHADAP SUATU PERBUATAN MELAWAN HUKUM YANG DILAKUKAN PIHAK DALAM AKTA NOTARIS (Studi Perkara Nomor 269/Pid.B/2015/PN.PDG) - Dia Ikhsan; Ismansyah Ismansyah (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2019)
Notary is one of the general officers authorized to create an authentic deed and other authorities as intended in the law. Notary can be called as a notary as a witness, suspect and accused in the event of an act against the law of the Outentic deed made in a notary public. The problem in this writing is 1) the role of notary as a witness against the deeds of the law committed by the parties in Notarial deed and 2) the judgment of judges in the verdict No. 269/Pid. B/2015/PN. PDG about the role of notary as a witness against the deeds of the law committed by the party in notarial deed. The research method used is a method of normative juridical approach empirical. The result of the study of notarial roles as witnesses of the Act against the law by the party in notarial deed came to fulfill the call as a witness in the interest of an investigation, a notary called for investigation Must be approved by the notary Honorary assembly and give information on what is provided by the Parties both oral and written in writing. Notary is called and needs his presence in the examination of criminal matters, in capacity as a general officer who makes authentic deed, it is necessary for his testimony of what is seen, heard and supporting evidence in the creation of authentic deeds The criminal matter, 2) the judgment of judges in the Decree No. 269/Pid. B/2015/PN. PDG about the role of notary as a witness against the deeds of the law conducted by the party in Notarial deed is a notary only as a witness called the court to be heard his description of the conduct of the law Done by the defendant is about the forgery of the SS signatures to make the letter of authorization selling and besides notary also called a witness from the notary party who is a witness in the making of the selling power deed.